Geriatric CO-mAnagement for Cardiology patients in the Hospital (G-COACH): study protocol of a prospective before-after effectiveness-implementation study. Issue 10 (21st October 2018) - Deschodt, Mieke; Van Grootven, Bastiaan; Jeuris, Anthony; Devriendt, Els; Dierckx de Casterlé, Bernadette; Dubois, Christophe; Fagard, Katleen; Herregods, Marie-Christine; Hornikx, Miek; Meuris, Bart; Rex, Steffen; Tournoy, Jos; et al.
Abstract : Introduction: Although the majority of older patients admitted to a cardiology unit present with at least one geriatric syndrome, guidelines on managing heart disease often do not consider the complex needs of frail older patients. Geriatric co-management has demonstrated potential to improve functional status, and reduce complications and length of stay, but evidence on the effectiveness in cardiology patients is lacking. This study aims to determine if geriatric co-management is superior to usual care in preventing functional decline, complications, mortality, readmission rates, reducing length of stay and improving quality of life in older patients admitted for acute heart disease or for transcatheter aortic valve implantation, and to identify determinants of success for geriatric co-management in this population. Methods and analysis: This prospective quasi-experimental before-and-after study will be performed on two cardiology units of the University Hospitals Leuven in Belgium in patients aged ≥75 years. In the precohort (n=227), usual care will be documented. A multitude of implementation strategies will be applied to allow for successful implementation of the model. Patients in the after cohort (n=227) will undergo a comprehensive geriatric assessment within 24 hours of admission to stratify them into one of three groups based on their baseline risk for developing functional decline: low-risk patients receive proactive consultation, high-risk patients will be co-managed by the geriatric nurse to prevent complications and patients with acute geriatric problems will receive an additional medication review and co-management by the geriatrician. Ethics and dissemination: The study protocol was approved by the Medical Ethics Committee UZ Leuven/KU Leuven (S58296). Written voluntary (proxy-)informed consent will be obtained from all participants at the start of the study. Dissemination of results will be through articles in scientific and professional journals both in English and Dutch and by conference presentations. Trial registration number: NCT02890927 .